Curricular Approaches to Transgender Health in Physician Assistant Education. (October 2020) - Rolls, Joanne; Davis, John; Backman, Richard; Wood, Tim; Honda, Trenton
Abstract : Purpose: According to the Williams Institute, 1.4 million U.S. adults identify as transgender. Many experience health care disparities. Professional organizations call for medical education to improve transgender care, but what curricula are being delivered is unknown. The goal of this study was to conduct the first comprehensive, national survey of transgender health care curricula in physician assistant (PA) education. Method: The authors sent a questionnaire to program directors (PDs) at all 236 U.S. PA programs in June 2018. They categorized programs as those that currently deliver at least 1 hour of transgender health content and those who do not (Teaching/Not Teaching). They examined differences between Teaching and Not Teaching programs using chi-square tests, and they evaluated comments for themes. Results: The response rate was 100%. Of the 236 programs, 202 (85.6%) teach transgender content and 34 (14.4%) do not. According to PDs, most transgender content was delivered in medical interviewing (44.1%) or women's health (31.4%) and the most common transgender health topics included differentiating between sex and gender and between behavior and identity (78.8%), followed by health disparities (77.5%) and barriers to care (75.0%). PDs most commonly cited a lack of time (51.3%) and faculty knowledge (35.6%) as barriers for teaching transgender health topics. Half of the PDs (50.4%) ranked transgender health as very or extremely important. The authors detected statistically significant differences between Teaching and Not Teaching programs based on geographic region ( P = .01), perceived importance ( P ⩽ .001), and presence of knowledgeable faculty ( P = .01). Presence of knowledgeable faculty was significantly associated with perceived importance ( P = .01). Conclusions: This is the first comprehensive, nationwide survey of transgender health education in U.S. PA programs. A key finding is that the presence of expert faculty is significantly associated with delivery and perceived importance of transgender health curricula. Abstract : Supplemental Digital Content is available in the text.